Terrorism and Radicalism Phenomenon and its impacts on International Peace and Stability (قضايا سياسية, 2023)
Terrorism and radicalism phenomena are not new rather they are as ancient as human existence. These phenomena have dire and significant impacts on international peace and security as they have started to spread internationally, noticeably during the last two decades of the twentieth century. Terrorism has undergone numerous fundamental changes after the 9/11 terrorist attacks, as it has become a global phenomenon that is not related exclusively to a certain state or a group of states and its effects can be felt by all the actors across the international arena. Indeed, terrorism and radicalism phenomena are among the most perilous challenges that the world faces today. The international community is dealing with a wide set of local, regional, and global transformations that caused a wide range of challenges and problems, among which terrorism and fundamentalism are the most dangerous ones as they threaten international peace and security and wreck the future of the next generations. This requires addressing the issues of terrorism and the exercise of violent extremism that sprouts from them. There is also a need to unite the efforts of various bodies, institutes, regional and international organizations, civil society organizations, and political and thought figures, each in its own capacity and roles, coordinating and complementing each other. These institutions should seek to practice their own significant role in order to diagnose the root causes and exogenous and endogenous impetus of terrorism.